Introduction: Margins and the State—Caste, 'Tribe' and Criminality in South Asia. (February 2020) - Gandee, Sarah; Gould, William
This introduction outlines some of the key historiographical debates concerning caste, 'tribe' and criminality, and their relationship to the modern state, in South Asia. Although these social categories have long, complex and often inter-related histories rooted in indigenous and precolonial ideas and institutions, they emerged most forcefully as categories of governance in the legal-political system of the colonial and postcolonial states. These categories remained highly unstable, however. There was a clear disjuncture between forms of 'colonial' knowledge which structured legal categorization and everyday negotiations and contestations of the same. Using the example of India's so-called 'criminal tribes' - the 200 or so communities declared as criminals 'by birth' under the Criminal Tribes Act (1871) during the colonial regime - we consider broader debates over the governing of 'colonial' categories, and subaltern agency and resistance in their making, as a way of interrogating the complex relationship between the 'margins' and the state.